Development of PjBL-STEM based student worksheets to improve mathematical literacy skills - Nurul Arfika; Kms Muhammad Amin Fauzi; E. Elvis Napitupulu (Inovasi Kurikulum, 2025)
The research was motivated by the low level of mathematical literacy among fifth-grade students at SD Negeri 068003 Medan and the urgent need for contextual and engaging learning materials. This study aims to develop Project-Based Learning (PjBL) student worksheets (LKPD) using a STEM approach to enhance elementary students' mathematical literacy skills. The study employed a Research and Development (RnD) method using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). The developed product was tested on 21 students through expert validation, limited trials, and effectiveness testing. The results showed that the LKPD met the criteria of being valid, practical, and effective in improving students’ mathematical literacy. The average score increased after implementation. This research is original in its integration of PjBL and the STEM approach into the development of LKPD tailored to the characteristics of elementary students. The implications suggest that contextual and project-based learning tools can serve as strategic solutions to improve mathematical literacy while fostering 21st-century skills.   Abstrak Latar belakang penelitian ini didasarkan pada rendahnya kemampuan literasi matematis peserta didik kelas V SD Negeri 068003 Medan serta kebutuhan akan perangkat ajar yang kontekstual dan menantang. Penelitian ini bertujuan untuk mengembangkan Lembar Kerja Peserta Didik (LKPD) berbasis Project-Based Learning (PjBL) dengan pendekatan STEM guna meningkatkan kemampuan literasi matematis peserta didik sekolah dasar. Penelitian ini menggunakan metode Research and Development (RnD) dengan model pengembangan ADDIE (Analysis, Design, Development, Implementation, and Evaluation). Produk yang dikembangkan diuji pada 21 peserta didik kelas V melalui validasi ahli, uji coba terbatas, dan uji efektivitas. Hasil penelitian menunjukkan bahwa LKPD yang dikembangkan memenuhi kriteria valid, praktis, dan efektif dalam meningkatkan kemampuan literasi matematis peserta didik. Capaian skor rata-rata meningkat setelah penggunaan LKPD. Penelitian ini memiliki nilai orisinalitas dalam integrasi model PjBL dengan pendekatan STEM dalam pengembangan LKPD yang disesuaikan dengan karakteristik peserta didik sekolah dasar. Implikasi dari penelitian ini menunjukkan bahwa perangkat ajar yang kontekstual dan berbasis proyek dapat menjadi solusi strategis untuk meningkatkan literasi matematis, sekaligus menumbuhkan keterampilan abad ke-21. Kata Kunci: literasi matematis; LKPD; PjBL; STEM